Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.5539/ijps.v10n2p102
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Wellbeing of Siblings of Children with Autism Spectrum Disorders: Sibling Efficacy, Positive and Negative Affect, and Coping Strategies

Abstract: Autism spectrum disorders (ASD) include pervasive developmental disorders characterised by communication deficits, difficulty with social understanding, and repetitive behaviors. Few studies have compared the efficacy, affect, and coping strategies of siblings of typically developing children with siblings of children with ASD. Typically developing siblings are understood to be at an increased risk of externalising and internalising problems. The current study examined whether siblings of children with ASD dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Similar findings have been previously found, where TD siblings reported mixed emotional experiences, including tension and frustration while also feeling a sense of empathy (Pavlopoulou, & Dimitriou, 2019;Petalas, 2012). Mixed findings were also reported in another study, where some children were found to be positively affected (e.g., high sense of self-concept) by having a sibling with ASD while others reported negative experiences (e.g., loneliness; low levels of prosocial behavior) (Habelrih et al, 2018). These results are likely due to diagnostic factors such as the severity of ASD, the amount of problematic behaviors by the sibling with ASD, and the family support given to the TD sibling (Meadan et al, 2010;Tomeny et al, 2017).…”
Section: Factors Influencing Emotional Experiencesupporting
confidence: 87%
See 2 more Smart Citations
“…Similar findings have been previously found, where TD siblings reported mixed emotional experiences, including tension and frustration while also feeling a sense of empathy (Pavlopoulou, & Dimitriou, 2019;Petalas, 2012). Mixed findings were also reported in another study, where some children were found to be positively affected (e.g., high sense of self-concept) by having a sibling with ASD while others reported negative experiences (e.g., loneliness; low levels of prosocial behavior) (Habelrih et al, 2018). These results are likely due to diagnostic factors such as the severity of ASD, the amount of problematic behaviors by the sibling with ASD, and the family support given to the TD sibling (Meadan et al, 2010;Tomeny et al, 2017).…”
Section: Factors Influencing Emotional Experiencesupporting
confidence: 87%
“…Given the focus on subjective experiences in qualitative inquiry, semi-structured interviews were used to explore the participants' perspectives. Key interview questions were developed based on a review of the literature (Benderix & Sivberg, 2007 ; Canha, 2010 ; Habelrih et al, 2018 ). These key questions were designed to explore the challenges faced by siblings of individuals with ASD, their coping strategies, and the effect of these challenges on their relationships (Appendix 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The family is considered a centre for exchanging experiences among its members so that they are influenced by each other and their positions converge and coalesce as an expression of the emotional participation of any member (al-Masa'deh, Younis, al-Zyoud & Homidi, 2020). Parents are the cornerstones and the main influencing factor on the individuals of the family, also the children are influencing with different ages, and any defect in building this family affects everyone within the family (Habelrih, Hicks & Vanstone, 2018). A root change in the psychological, social, and behavioural pathway of the family can occur when discovered a disability of child in the family (Begum & Mamin, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A root change in the psychological, social, and behavioural pathway of the family can occur when discovered a disability of child in the family (Begum & Mamin, 2019). The brothers and sisters of a child with disabilities will express their concern at the level of consciousness or unconsciousness due to the extra and special effort needed of their brother with disabilities, while the special needs of them are neglected (Habelrih et al, 2018). As a result, the existence of a disabled child in the family, as well as the unwanted features he possesses, is a source of stress for his disabled brother (llias et al, 2018).…”
Section: Introductionmentioning
confidence: 99%